Role of Consumer Protection Organization in Awareness of Consumer Goods in Libyan Market (An Analytical Study of Consumers’ Opinions on Mahari Market, Tripoli( - Mousbah Salem Ahmouda , Mohammed Abu baker boker , Ahmed saad ahmed (Journal of Pure & Applied Sciences, 2019)
Consumer protection conceders is one of the most important issues of those who are concerned to in this field, because of its impact on different levels.Therefore,the study aimed to analyze and measuring the impact of awareness campaigns carried out by the consumer protection organizations to insuring the safety of Libyan consumer. A survey was used consisting of 15 phrases and a random sample of 160 people was chosen from the customers who are interested in MAHRY market, to study the relationship between independent and dependent variables. The data were analyzed by statistical model SPSS. The study found that, there is no statistically significant impact of awareness campaigns for consumer protection organizations in Libya towards the Libyan consumer in relation to the consumer of consumer goods. The study also showed that, the process of consumer awareness, especially regards to consumer goods has negative effects on the rights of the Libyan consumer. Lastly, study recommended that, there is persistent need to activate the role of consumer protection organizations throughout enhancing the media integration between organizations concerned with consumer awareness protection and the media. Educating the consumer through the development of awareness campaigns, awareness programs and media plans.